2002
DOI: 10.1200/jco.20.5.1389
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Murine 131I-Labeled Antitenascin Monoclonal Antibody 81C6 Administered Into Surgically Created Resection Cavities of Patients With Newly Diagnosed Malignant Gliomas

Abstract: Median survival achieved with (131)I-labeled 81C6 exceeds that of historical controls treated with conventional radiotherapy and chemotherapy, even after accounting for established prognostic factors including age and Karnofsky performance status. The median survival achieved with (131)I-labeled 81C6 compares favorably with either (125)I interstitial brachy-therapy or stereotactic radiosurgery and is associated with a significantly lower rate of reoperation for radionecrosis. Our results confirm the efficacy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(87 citation statements)
references
References 29 publications
0
86
0
1
Order By: Relevance
“…8 -14 Because the clinical outcome of patients with GBM still is very poor, several groups started treating patients with GBM using radiolabeled monoclonal anti-TN-C antibodies, which were placed into the postoperative cavity using an indwelling (Rickam or Omaya) catheter. [15][16][17][18][19][20][21][22][23][24] Riva et al 15 reported that the average overall survival of 9 -10 months in patients with GBM could be prolonged to 19 -25 months using radioimmunotherapy. No systematic data exist in the literature about the frequency and cellular localization or the relation of TN-C to overall survival in patients with other brain tumors, such as low-grade astrocytomas, meningiomas, and schwannomas.…”
Section: Resultsmentioning
confidence: 99%
“…8 -14 Because the clinical outcome of patients with GBM still is very poor, several groups started treating patients with GBM using radiolabeled monoclonal anti-TN-C antibodies, which were placed into the postoperative cavity using an indwelling (Rickam or Omaya) catheter. [15][16][17][18][19][20][21][22][23][24] Riva et al 15 reported that the average overall survival of 9 -10 months in patients with GBM could be prolonged to 19 -25 months using radioimmunotherapy. No systematic data exist in the literature about the frequency and cellular localization or the relation of TN-C to overall survival in patients with other brain tumors, such as low-grade astrocytomas, meningiomas, and schwannomas.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these markers should not be disregarded. Tenascin is a glycoprotein responsible for producing gliogenic precursors and has been a target for radioimmunotherapy in brain tumors (65,158). The tenascin c (TNC) gene on chromosome 9 seems upregulated in infant ependymomas (76), and its protein expression seems relatively high in pediatric cases (35), whereas the presence of intercellular tenascin has been identified as an adverse prognostic marker in an albeit small immunohistochemical study of pediatric ependymomas (129).…”
Section: Immunohistochemical and Genomic Markersmentioning
confidence: 99%
“…Differences in fluorescent intensities between the two markers along the length of each chromosome subsequently identify regions of genetic gain and loss within the tumor genome. A review of literature on CGH analyses of ependymoma since the year 2000 revealed 13 studies, collectively evaluating 303 primary tumors with genomic abnormalities (58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70). We have undertaken a comparative meta-analysis of this cohort.…”
Section: Molecular Distinctions Between Pediatric and Adult Ependymomasmentioning
confidence: 99%
“…These ECM components are highly abundant in tumours and are often more stable than antigens located on the cell surface of tumour cells. Radio labelled antibodies specific to TNC (Tenascin-C domain C) domains A1 and D have been used successfully in the clinic to treat glioma and lymphoma [34]. The EDB-targeting antibody L19 has been used as a vehicle for TNFα (Alpha) and has been shown to induce necrosis in tumours.…”
Section: Influence Of Tumour-associated Fibroblasts On Tumour Behaviourmentioning
confidence: 99%